The Future is Embedded: The Persistence of Physical Systems in the Age of Artificial Intelligence - Karpinski, Thobias (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.16414, 2025)
Artificial intelligence (AI) has been accelerating the automation of tasks once performed exclusively by humans, especially in programming, where AI assistants are already writing code with high efficiency. This progress raises questions about the obsolescence of the traditional programmer. On the other hand, embedded systems due to their interaction with the physical world, sensors, actuators, and unpredictable conditions remain essential. This article, of bibliographic and critical nature, analyzes how the rise of AI is redefining work in technology while preserving the relevance of intelligent physical systems. It also discusses emerging professions in this field and the social and educational impacts, with a focus on Latin America. The conclusion highlights that professionals capable of integrating hardware and software the so-called “orchestrators of reality” will play a leading role in a scenario of hyperautomation.